1977
DOI: 10.1039/p19770001849
|View full text |Cite
|
Sign up to set email alerts
|

Keten. Part 15. Reactions of diphenylketen with some N-alkyl nitrones

Abstract: By Anthony F. Gettins, David P. Stokes, Giles A. Taylor," and (in part) Christopher B. Judge, Department N-(Fluoren-9-ylidene)alkylamine N-oxides ( I ) react with diphenylketen to give spiro-oxazolidinones ( 2 ) and spiro-azetidinones (1 3). The adduct (2d) dissociates thermally to give the ylide ( 9 ) . The N-oxides (1) behave like normal nitrones in cycloaddition reactions with dipolarophiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…( 8) e (9), promoted by the ability of R in (8) to delocalise negative charge. This suggestion would seemingly accord with the observation that tetrahydroisoquinoline-1 -carboxylic acid (20), in which the carboxy group is in a benzylic site, reacts (DMF, 120 "C, 1 h) with benzaldehyde and N-methylmaleimide to give a 1.2: 1.7: 1.0: 1.9 mixture of (21a)-(24a),' i.e., a 1: 1 ratio of adducts derived from anti-(25a)-and sjw-( 26)-dipoles.…”
Section: C-vclic Secondary %-Amino Acids With a Benzylic Carboxysupporting
confidence: 85%
See 2 more Smart Citations
“…( 8) e (9), promoted by the ability of R in (8) to delocalise negative charge. This suggestion would seemingly accord with the observation that tetrahydroisoquinoline-1 -carboxylic acid (20), in which the carboxy group is in a benzylic site, reacts (DMF, 120 "C, 1 h) with benzaldehyde and N-methylmaleimide to give a 1.2: 1.7: 1.0: 1.9 mixture of (21a)-(24a),' i.e., a 1: 1 ratio of adducts derived from anti-(25a)-and sjw-( 26)-dipoles.…”
Section: C-vclic Secondary %-Amino Acids With a Benzylic Carboxysupporting
confidence: 85%
“…1 755, 1 680 (amide), 750,740, and 690 cm-'; 6 2.86 (1 H, m, lla-H), 2.96-3.04 (1 H, m, llP-H), 3.01 (3 H, s, 2-Me), 3.17(1 H,dd, J 4 a n d 16Hz, lla-H),3.24(1 H,dd, J 7 a n d 9 H z , 4-H), 3.27 ( 1 H,d,J 15 Hz,3.363.43 (2 H,m,4.07 (1 H,d,J15Hz,6-H),6.29(1H,dd,J9and16Hz, olefinic-H), 6.73 (1 H,d,J 16 Hz,m,ArH) (20). and 104 (33).…”
Section: L 1 B-octahydro-2-methyi-4-(2-phenyl-etheny1)-1 H-pyrrolomentioning
confidence: 99%
See 1 more Smart Citation
“…[9] Building upon this precedent, and the utility of 3-alkyl-3-aryloxindoles ( 3 ) as valuable synthetic intermediates that can be derivatized to numerous natural products and medicinal targets, [10] we reported [6] that treatment of nitrone 1a , derived from Garner’s aldehyde, [11] with an alkylarylketene ( 2 ) afforded, after aqueous workup, oxindoles ( S )- 3a – c in 80–88% yield and 81–90% ee (Table 1, entries 1–3). Further experimental optimization of this process showed that nitrones derived from Garner’s aldehyde are critical to achieve high asymmetric induction, with increasing size of the oxazolidine N -substituent ( 1b – c ) consistently leading to improved enantio-selectivities.…”
mentioning
confidence: 99%
“…The initially proposed reaction pathways for this process (pathway I, Scheme 1), [69] involved the ketene (shown here as 2a ) reacting as an electrophile towards the nitrone (shown here as 4 ), giving, after rearomatization, the experimentally isolable imino acids 5 bearing a quaternary carbon. Subsequent hydrolysis and cyclization afford the oxindole products 3 .…”
mentioning
confidence: 99%